2018
DOI: 10.1016/j.chiabu.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of implicit encouragement and the putative confession on children’s memory reports

Abstract: The current study tested the effects of two interview techniques on children's report productivity and accuracy following exposure to suggestion: implicit encouragement (backchanneling, use of children's names) and the putative confession (telling children that a suspect "told me everything that happened and wants you to tell the truth"). One hundred and forty-three, 3-8-year-old children participated in a classroom event. One week later, they took part in a highly suggestive conversation about the event and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Conversely, consistent with previous research (Cleveland et al, 2018, Hershkowitz, 2002Lamb, Hershkowitz, Sternberg, Boat, & Everson, 1996), back-channel utterances increased the productivity of disclosures but not disclosures themselves, and thus could be characterized as recall enhancement. Similarly, narrative practice rapport building has been found to increase the productivity of disclosures (Sternberg et al, 1997), but had not been found CHILDREN'S RECALL to increase the likelihood that transgressions will be disclosed Yi & Lamb, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Conversely, consistent with previous research (Cleveland et al, 2018, Hershkowitz, 2002Lamb, Hershkowitz, Sternberg, Boat, & Everson, 1996), back-channel utterances increased the productivity of disclosures but not disclosures themselves, and thus could be characterized as recall enhancement. Similarly, narrative practice rapport building has been found to increase the productivity of disclosures (Sternberg et al, 1997), but had not been found CHILDREN'S RECALL to increase the likelihood that transgressions will be disclosed Yi & Lamb, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The instruction has been shown to increase true disclosures of transgressions Quas et al, 2018;Rush et al, 2017;Stolzenberg, McWilliams, & Lyon, 2017) and to decrease false claims (Rush et al, CHILDREN'S RECALL 2017). Furthermore, the putative confession has not been found to increase false reports among children who have been suggestively questioned (Cleveland et al, 2018;Rush et al, 2017).…”
Section: Putative Confessionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, in failing to provide specific details about the suspect's statements, the instruction avoids the suggestive effects of telling children about other witnesses' reports (Garven, Wood, Malpass, & Shaw, ) or asking children to speculate or pretend (Schreiber, Wentura, & Bilsky, ). Indeed, the PC has not been found to increase false reports when a transgression did not occur (Lyon et al, ; Quas et al, ), even among children suggestively questioned (Cleveland, Quas, & Lyon, ; Rush et al, ). Additionally, the PC has been effective among children who are less responsive to a request that they promise to tell the truth, including younger and maltreated children (McWilliams et al, n.d.).…”
Section: The Putative Confession Instructionmentioning
confidence: 99%